Rezim Kebenaran dan Kuasa Negara: Analisis Wacana Kritis atas Kontroversi Kuota Haji Khalid Basalamah - Ikmal Maulana Akbar; Dzulfikar Adirais; Dono Darsono (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This article analyzes the 2024 Hajj quota controversy involving Khalid Basalamah through the lens of Michel Foucault's theory of truth regimes. Using a Critical Discourse Analysis (CDA) approach, this study demonstrates how the state, bureaucracy, and digital media collectively produce